2021
DOI: 10.1002/htj.22236
|View full text |Cite
|
Sign up to set email alerts
|

Entropy generation in a micropolar fluid past an inclined channel with velocity slip and heat flux conditions: Variation parameter method

Abstract: An investigation is carried out on the analysis of entropy on the flow of non-Newtonian fluid, in particular, micropolar fluid past an inclined channel. To enhance the fluid properties, velocity and thermal slip conditions are taken into consideration. At the outset, the novelty of the present investigation lies on the analysis of entropy generation that occurs due to the temperature differences between the media. The governing nonlinear equations are transformed to nonlinear ODE by the use of suitable transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…MHD flow along with different parameters has been investigated by many researchers, which are relevant to the present study and are included. [28][29][30][31][32][33][34] One cannot ignore the boundary layer flow of nano-liquids, where the magnetic field is taken inclined because of its application in magneto-therapy, cancer therapy, magnetic cell separation, drug delivery and various physiological processes. Hayat et al, 35 reported the impact on heat transfer of inclined magnetic fields and various parameters of the Williamson fluid flow through a channel.…”
mentioning
confidence: 99%
“…MHD flow along with different parameters has been investigated by many researchers, which are relevant to the present study and are included. [28][29][30][31][32][33][34] One cannot ignore the boundary layer flow of nano-liquids, where the magnetic field is taken inclined because of its application in magneto-therapy, cancer therapy, magnetic cell separation, drug delivery and various physiological processes. Hayat et al, 35 reported the impact on heat transfer of inclined magnetic fields and various parameters of the Williamson fluid flow through a channel.…”
mentioning
confidence: 99%
“…In view of the above research title, other recent and relevant published work can be found in. 4752…”
Section: Introductionmentioning
confidence: 99%
“…In view of the above research title, other recent and relevant published work can be found in. [47][48][49][50][51][52] Motivated by the gaps in the previous research work and considering the fact that no research work on the boundary layer flow has considered electromagnetohydrodynamic flow of hyperbolic tangent nanofluid featuring velocity slip and thermo diffusion. Hence, the current study explores features of a hyperbolic tangent nanofluid along a radiative Riga stretching surface with the Soret effect, heat source, velocity slip, suction/injection, and activation energy, all of which are inspired by the aforementioned literature.…”
Section: Introductionmentioning
confidence: 99%
“…Tlili et al 3 examined the consequences of the Hall effect on water‐based MHD Couette–Poiseuille nanofluid flowing in a revolving channel and showed the powerful influence on fluid flow by viscosity and magnetic field. The outcome of thermal radiation on micropolar liquid flowing in an oblique channel making use of finite element technique and found that rise in the rate of entropy generation with Eckert number by Shashikumar et al 4 Mathur et al 5 looked into entropy generation in a non‐Newtonian micropolar fluid flowing through an inclined microchannel to improve the properties of fluids and the result revealed that microrotation profiles its twin characteristics with the addition of inclined angle.…”
Section: Introductionmentioning
confidence: 99%